2016
DOI: 10.1016/j.bbabio.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical transmission in I-Band segments of the mitochondrial reticulum

Abstract: Within the mitochondrial reticulum of skeletal muscle, the I-Band segments (IBS) traverse the cell and form a contiguous matrix with the mitochondrial segments at the periphery (PS) of the cell. A tight electrical coupling via the matrix between the PS and IBS has been demonstrated. In addition, oxidative phosphorylation complexes that generate the proton motive force (PMF) are preferentially located in the PS, while Complex V, which utilizes the PMF, is primarily located along the IBS. This has led to the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In the classic 2-mitochondrial population model, a collection of peripheral mitochondria has decreased oxidative capacity compared with the physically distinct pool of mitochondria in the myofibrillar space (75)(76)(77). In the newly emerging view of mitochondria, in which mitochondria are thought to exist in a dynamic reticulum extending from the sarcolemma to the myofibrils and actively undergo fusion and fission in continuous networks throughout the cell, peripheral segment mitochondria have a greater abundance of proton motive proteins, whereas the connected intermyofibrillar mitochondria located in the I-band have more ATP-generating proteins for use by sarcomeres (56,78). In the current study, the abnormal spherical mitochondria in the peripheral space of injured muscles at 30 and 60 d after rotator cuff tear could reflect a mitochondrial network that has been mechanically and biochemically disrupted; this is supported by observations in yeast in which the small mitochondria that bud off of larger networks of mitochondria have a spherical appearance (79).…”
Section: Discussionmentioning
confidence: 99%
“…In the classic 2-mitochondrial population model, a collection of peripheral mitochondria has decreased oxidative capacity compared with the physically distinct pool of mitochondria in the myofibrillar space (75)(76)(77). In the newly emerging view of mitochondria, in which mitochondria are thought to exist in a dynamic reticulum extending from the sarcolemma to the myofibrils and actively undergo fusion and fission in continuous networks throughout the cell, peripheral segment mitochondria have a greater abundance of proton motive proteins, whereas the connected intermyofibrillar mitochondria located in the I-band have more ATP-generating proteins for use by sarcomeres (56,78). In the current study, the abnormal spherical mitochondria in the peripheral space of injured muscles at 30 and 60 d after rotator cuff tear could reflect a mitochondrial network that has been mechanically and biochemically disrupted; this is supported by observations in yeast in which the small mitochondria that bud off of larger networks of mitochondria have a spherical appearance (79).…”
Section: Discussionmentioning
confidence: 99%
“…We note that the observation of lower energetic capacity at the highest levels of demand is more consistent with intrinsic defect in oxidative phosphorylation when challenged above a certain threshold. For example, studies in mice have found that skeletal muscle mitochondria are organized in a highly reticular structure around the myofibrils (Glancy et al., ; Patel, Glancy & Balaban, ; Porter et al., ). Glancy et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the classical two mitochondrial population model, a collection of peripheral mitochondria have decreased oxidative capacity compared to the physically distinct pool of mitochondria in the myofibrillar space (70)(71)(72). In the newly emerging view of mitochondria, where mitochondria are thought to exist in a dynamic reticulum extending from the sarcolemma to the myofibrils, and actively undergoing fusion and fission in continuous networks throughout the cell, peripheral segment mitochondria have a greater abundance of proton motive proteins, whereas the connected intermyofibrillar mitochondria located in the I-band have more ATP generating proteins for use by sarcomeres (51,73). In the current study, the abnormal spherical mitochondria in the peripheral space of injured muscles at 30 and 60 days after rotator cuff tear could reflect a mitochondrial network that has been mechanically and biochemically disrupted, and this is supported from observations in yeast in which the small mitochondria that bud off of larger networks of mitochondria have a spherical appearance (74).…”
Section: Discussionmentioning
confidence: 99%